Examining Teachers’ Perceptions of School Effectiveness in Public Primary and Secondary Schools - Martin, Andre Anthony (American Journal of Social Sciences and Humanities, 2022)
The purpose of this study was to examine teachers’ perceptions of School Effectiveness based on school level, sex and role in management in public schools in Grenada. Using a quantitative descriptive correlational research design, a survey was administered to a sample of 729 primary and secondary schools’ teachers using a 58-item Likert scale questionnaire. Principal Component Analysis identified 5 components of School Effectiveness and this result was analysed using descriptive statistics, the independent samples t-test, and the Pearson Moment Corelation. The findings indicated that the teachers’ perceptions of School Effectiveness were highly positive and moderately positive in primary and secondary schools respectively. The t-test revealed significant differences between primary and secondary school teachers, however, none were detected based on sex and role in management. The findings also revealed that there were significant substantial direct relationships among the components of School Effectiveness. This study establishes a discourse on the perceptions of School Effectiveness, adding to the School Effectiveness literature in a Caribbean context. It further suggests that schools should focus on key elements of School Effectiveness to lead school to development, however, the initiative is for practitioners to decide what key components of school effectiveness should be the highlighted in their school development plan.